AN ANALYSIS OF SPEECH ACT IN THE GROWN UPS MOVIE - Lida Marbun; Nurma Dhona Handayani (JEE (Journal of English Education), 2020)
This research discussed about the analysis of speech act used in the Grown Ups movie. This research revealed the types of speech act that found in the Grown Ups during the movie. The researcher applied the qualitative descriptive method because it was dealt with the description analysis by using words. Observation method used to collect the data. The researcherchose this movie because it was popular in the 20’s century and there were many speech acts reflected in this movie. As the result, it was found that were 30 utterances of speech acts in Grown Ups movie. From the 30 data that researcher collected, the main characters most expressed the types of speech act. They are 6 locutionary acts, 15 illocutionary acts, and 9 perlocutionary. Based all the data above, it can be concluded the most used speech act found in this data was illocutionary act. The next was perlocutionary act. Then the last was locutionary act.